Distance Learning for Young Students During the Covid-19 Epidemic in Slovenia - Puhalj, Stojan; Šimunič, Boštjan; Pišot, Saša; Planinšec, Jurij (Revija za elementarno izobraževanje, 2022)
The aim of the study was to investigate how physical education classes were conducted during remote schooling. The results confirm the poorer quality and duration of physical education classes during remote schooling. Our findings also coincide with the findings of other studies, which show that during the COVID-19 pandemic, children’s physical/sports activity, as well as their motor functions, decreased dramatically. This study provides clear answers to all responsible stakeholders that remote schooling is not an appropriate measure from the point of view of ensuring the conditions for healthy development of children.
Keywords: COVID-19, children, isolation, physical activity, physical education